Analisis Pengaruh Tingkat Pendidikan, Upah Minimum Provinsi dan Jumlah Industri Terhadap Kesempatan Kerja di Provinsi Jawa Timur tahun 1995-2020 - Fara Eka Wahyuni Fara Eka Wahyuni; Wahyu Hidayat Riyanto; Setyo Wahyu Sulistyono (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
In national economic development, there is a gap between the growth of the workforce and the willingness of various economic sectors to absorb labor, making job opportunities still a major problem in the economy. Employment opportunities are influenced by several factors, namely the level of education, provincial minimum wage , and the number of industries. The purpose of this study was to determine the effect and analyze the variables of Education level, Provincial Minimum Wage , and Number of Industries on Employment Opportunities in East Java Province 1995-2020. This study uses the Multiple Regression analysis tool method with time series. The results of the study show that simultaneously the variables of Education Level, Provincial minimum wage, and Number of Industries have a significant effect on Employment Opportunities in East Java Province in 1995-2020. The coefficient of determination (R²) indicates that 95 percent of employment opportunities and the remaining 5 percent are explained by other variables not examined. Partially the level of education, Provincial Minimum Wage, and Number of Industries have a significant effect on Job Opportunities in East Java Province.